2023
DOI: 10.1038/s41598-023-30060-w
|View full text |Cite
|
Sign up to set email alerts
|

Primary ILM peeling during retinal detachment repair: a systematic review and meta-analysis

Abstract: Epiretinal membrane (ERM) formation is a known postoperative complication following retinal detachment (RD) repair surgery. Prophylactic peeling of the internal limiting membrane (ILM) during surgery has been shown to reduce the risk of developing postoperative ERM formation. Some baseline characteristics and degrees of surgical complexity may act as risk factors for ERM development. In this review we aimed to investigate the benefit of ILM peeling in patients without significant proliferative vitreoretinopath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…In a study that examined the incidence of epiretinal membrane formation after successful primary RRD repair, postoperative epiretinal membranes developed in 15% and 28.5% of patients in the scleral buckling and PPV groups, respectively [ 113 ]. Similarly, a meta-analysis revealed that the incidence of epiretinal membrane formation was 7.1% and 5.2% in patients treated with PPV and scleral buckling alone, respectively [ 114 , 115 ]. Evidence suggests that peeling the ILM during surgery can reduce the likelihood of epiretinal membrane development [ 115 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study that examined the incidence of epiretinal membrane formation after successful primary RRD repair, postoperative epiretinal membranes developed in 15% and 28.5% of patients in the scleral buckling and PPV groups, respectively [ 113 ]. Similarly, a meta-analysis revealed that the incidence of epiretinal membrane formation was 7.1% and 5.2% in patients treated with PPV and scleral buckling alone, respectively [ 114 , 115 ]. Evidence suggests that peeling the ILM during surgery can reduce the likelihood of epiretinal membrane development [ 115 ].…”
Section: Discussionmentioning
confidence: 99%